A meshfree method for fully coupled analysis of flow and deformation in unsaturated porous media. (13th April 2012) - Khoshghalb, A.; Khalili, N.
SUMMARY: A meshfree algorithm is proposed for the fully coupled analysis of flow and deformation in unsaturated poro‐elastic media. A brief description of the governing differential equations is presented followed by the spatial discretization of the governing equations using the Galerkin approach and the radial point interpolation method. Temporal discretization is achieved using a three‐point approximation technique with second order accuracy. Particular attention is given to the determination of constitutive coefficients and effective stress parameters of the medium taking into account hydraulic hysteresis. Application of the model to several experimental data is demonstrated. Good agreement is obtained between the numerical and experimental results in all cases highlighting the ability of the proposed model in capturing the volume change and suction dependency of the model parameters as well as the coupled behaviour of unsaturated porous media subject to hydraulic hysteresis. Copyright © 2012 John Wiley & Sons, Ltd.